Atrial fibrillation patterns are associated with arrhythmia progression and clinical outcomes. Issue 19 (17th March 2018) - B Schnabel, Renate; Pecen, Ladislav; Engler, Daniel; Lucerna, Markus; Sellal, Jean Marc; Ojeda, Francisco M; De Caterina, Raffaele; Kirchhof, Paulus
Abstract : Objectives: Determinants of atrial fibrillation (AF) patterns and of progression of earlier forms to permanent AF, and their relationship with outcome are still poorly understood. Methods: We examined AF patterns (paroxysmal, persistent and permanent), rate and predictors of AF progression, and outcomes in the PREFER (PREvention oF thromboembolic events-European Registry) in AF. The primary analysis was performed in the PREFER in AF prolongation dataset (n=3223 patients with AF with a complete 1-year follow-up, mean age 72±9 years, 40% women). Sensitivity analyses were performed using the PREFER in the AF study (n=6390 patients). Results: AF progressed to more persistent types in 506 patients (17%). Permanent AF was associated with development of heart failure at 1 year (OR 1.80, 95% CI 1.06 to 3.07, p=0.03) compared with paroxysmal AF, which was confirmed in the entire cohort. In multivariable-adjusted models, sinus rhythm at baseline, AF duration, cardioversion, hyperthyroidism, valvular heart disease, diabetes mellitus and heart failure were predictors of AF progression (area under the receiver operating characteristic curve 0.60, 95% CI 0.57 to 0.63). Results were similar when we restricted analyses to patients with AF duration <1 year. AF progression showed an association with coronary events over 1 year (OR 2.27, 95% CI 1.22 to 4.19, p=0.0074). Conclusions: Permanent AF at baseline was associated with incident heart failure. A substantial proportion of well-managed patients with AF showed AF progression over 1 year. AF progression itself was not strongly related to outcome and may indicate the need to refine the current classification of AF types to enhance clinical utility.